Development of a tourism coopetition model: A preliminary Delphi study. (December 2018) - Chim-Miki, Adriana F.; Batista-Canino, Rosa M.
Abstract: While coopetition behavior has been explored in various studies from different points of view, tourism coopetition and models to measure coopetition capacity have not received similar attention. In this study, we aim to develop an explanatory model of coopetition in tourism destinations. A theoretical review provided a list of factors and environmental conditions to favor coopetition behavior. Later, a Delphi technique was used to better define the model of Tourism Coopetition. An expert panel analyzed a list of 47 indicators derived from coopetition literature grouped in seven factors and narrowed them down to the 30 most important indicators of coopetition related to tourism destinations. The findings show that a coopetition model in a tourism destination is determined by seven factors: co-location, associationism, competition, cooperation, strategic management, co-entrepreneurship, and co-production. This research has a twofold implication: it provides a means of monitoring the strengths and weaknesses of a tourism destination toward coopetition behavior and therefore, it can be used to optimize stakeholder relationships to increase the competitiveness in the hospitality and tourism industry, as well as inspiring other researchers in this field.